RED GINGER STEW LOWERS BLOOD PRESSURE IN ELDERLY WITH HYPERTENSION IN BENGKULU CITY - Hendri Heriyanto; Bayu Adhi Nugraha; Efrizon Hariadi (Poltekkes Kemenkes Bengkulu, 2022)
Hypertension is a state of increased blood pressure that exceeds the normal threshold of 120/80 mmHg, namely systolic exceeding 140 mmHg and diastolic exceeding 90 mmHg. Hypertension is one of the special concerns of world health, especially in developing countries because it is the highest cause of death worldwide. This study aims to determine the effect of steeping red red ginger on changes in blood pressure in the elderly with hypertension in the work area of the Sawah Lebar Health Center, Bengkulu City. The research design used a quasi-experimental pre-post test with control group design. To find the sampling used sampling technique is random sampling. The number of respondents 44 people consisting of 22 respondents for each group. The treatment given was boiled red ginger water while the control group only boiled ordinary ginger. The data collection instrument used a tension meter and a questionnaire. The results of statistical tests using man whitney on systolic blood pressure obtained ap value of 0.001 (p value a 0.05) on diastolic blood pressure, p value of 0.001 (p value a 0.05). So that it can be interpreted that there is an effect of therapeutic intervention of red ginger boiled water on reducing blood pressure in patients with hypertension